2024
DOI: 10.1186/s12875-024-02298-4
|View full text |Cite
|
Sign up to set email alerts
|

The association of family doctor contract service and patient trust in doctor: evidence from twenty-five village clinics of three counties in rural China

Linni Gu,
Xiaoying Wang,
Donghua Tian

Abstract: Background China is implementing the family doctor (FD) system to reform the primary healthcare (PHC). The family doctor contract service (FDCS) policy plays a crucial role in this system implementation, aiming to transform the doctor-patient relationship and enhance PHC quality. This study aims to investigate the impact of FDCS on the doctor-patient relationship in PHCs using field research methodology. Method The field research methodology was em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Li et al [ 18 ] conducted a cross-sectional survey of 16 patients with chronic diseases in 847 primary care organizations in Jilin Province and found that contractual services could directly or indirectly influence patients’ perceived engagement, which in turn influenced the relationship between doctors and patients. Gu et al [ 38 ], based on questionnaire data from 574 rural clinics in three counties in China, reported that the implementation of family physician contract services played a key role in changing doctor-patient relationships and helped to attract more patients to primary care centers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Li et al [ 18 ] conducted a cross-sectional survey of 16 patients with chronic diseases in 847 primary care organizations in Jilin Province and found that contractual services could directly or indirectly influence patients’ perceived engagement, which in turn influenced the relationship between doctors and patients. Gu et al [ 38 ], based on questionnaire data from 574 rural clinics in three counties in China, reported that the implementation of family physician contract services played a key role in changing doctor-patient relationships and helped to attract more patients to primary care centers.…”
Section: Literature Reviewmentioning
confidence: 99%